The anatomical relationship between the axillary artery and vein investigated by radial coronary angiography - KEPEZ, ALPER; MUTLU, BÜLENT; ATAŞ, HALİL; ERDOĞAN, OKAN (WILEY, 2018)
AimsTo reduce the risk of inadvertent arterial puncture and bleeding, we aimed to define a safe puncture site by demonstrating the relation of the axillary artery and vein. MethodsThe anatomical course and relation as well as crossover sites of the axillary artery and vein, the presence of small arterial bridges over the axillary vein, and validation of commonly preferred axillary venous puncture sites were determined by simultaneous ipsilateral venography in patients (n=111; 80 men, age 60 10 years) who underwent coronary angiography by radial artery access. ResultsThe axillary vein was detected at the first costa-clavicular intersection in 62% and at the second anterior and third posterior costal intersection in 60% of the patients. Small arterial bridges over the axillary vein were observed in 77% of the patients and more frequently in females and body mass index 25kg/m(2) (P=0.034 and P=0.03, respectively). The axillary artery crossed the vein in 24% of the patients and almost always within the region close to the first costa-clavicular intersection site. ConclusionOur study demonstrated a high crossover rate (24%) of axillary artery and vein and a high degree of variation in the course of axillary vein. Small arterial bridges over the axillary vein were observed in 77% of the patients.
Keywords: axillary artery and vein; bleeding; pacemaker; puncture site; vein access; DEFIBRILLATOR LEADS IMPLANTATION; PACEMAKER IMPLANTATION; CONTRAST VENOGRAPHY; EARLY COMPLICATIONS; WARFARIN THERAPY; PUNCTURE; EXPERIENCE; CHAMBER; SAFE